ISOLASI PROTEIN KACANG MERAH DAN KACANG HIJAU MENGGUNAKAN METODE ASAM BASA DIKOMBINASIKAN DENGAN PROSES ENZIMATIS - Slamet Hadi Kusumah; Robi Andoyo; Tita Rialita (Jurnal Teknologi dan Industri Pangan, 2021)
Red beans (Phaseolus vulgaris L.) and greens beans (Phaseolus raditus L.) proteins contain high amount of essential amino acids lysine and leucine. The study aimed to determine the optimum conditions for protein isolation process from red beans and green beans flour to produce the highest protein content. Additionally, an enzymatic hydrolysis was aimed to produce isolates or protein concentrates of red beans and green beans with good digestibility. The research method used was the Response Surface Methodology (RSM) Box-Behnken Design with Design Expert 10. The variables used in this process were extraction temperature (30-50°C), extraction pH (8.50-9.50), and time extraction (30-60 minutes). The results showed that the optimum conditions for the extraction of red beans protein were extraction pH of 8.60, temperature of 30°C, and time of 30.1 minutes, with the resulting protein content of 86.88±1.38% with and a validity value of 0.91. Meanwhile, the optimum conditions for the green beans protein extraction process were extraction pH of 8.83, extraction temperature of 30°C, extraction time of 30 minutes which yielded protein content of 88.27±1.08% and a validity value of 0.97. Enzymatic hydrolysis using of 3% (w/w) bromelain enzyme on red bean and mung bean protein concentrate powder was able to increase protein digestibility by 15.61 and 14.51%, respectively.